2000
DOI: 10.1111/j.1529-8027.2000.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on peripheral nerve function and regeneration

Enrique Verdú,
Dolores Ceballos,
Jorge J. Vilches
et al.

Abstract: Aging deeply influences several morphologic and functional features of the peripheral nervous system (PNS). Morphologic studies have reported a loss of myelinated and unmyelinated nerve fibers in elderly subjects, and several abnormalities involving myelinated fibers, such as demyelination, remyelination and myelin balloon figures. The deterioration of myelin sheaths during aging may be due to a decrease in the expression of the major myelin proteins (P0, PMP22, MBP). Axonal atrophy, frequently seen in aged ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
288
1
13

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(318 citation statements)
references
References 135 publications
16
288
1
13
Order By: Relevance
“…In the peripheral target, measures in human of intraepidermal nerve fiber density showed no significant change in epidermal fiber density with age, except when comparison of aged samples was made to the highest values in the youngest subjects [25,27] (though see [7,14]). In 18-month old mice, innervation to the epidermis showed only a moderate loss (10-15%) in nerve fiber density [37]. Interestingly, this loss of peripheral nerve fibers in very old rodents does not appear to reflect a loss of neurons in cervical and lumbar DRG.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In the peripheral target, measures in human of intraepidermal nerve fiber density showed no significant change in epidermal fiber density with age, except when comparison of aged samples was made to the highest values in the youngest subjects [25,27] (though see [7,14]). In 18-month old mice, innervation to the epidermis showed only a moderate loss (10-15%) in nerve fiber density [37]. Interestingly, this loss of peripheral nerve fibers in very old rodents does not appear to reflect a loss of neurons in cervical and lumbar DRG.…”
Section: Introductionmentioning
confidence: 88%
“…Functional studies in several species have shown that impairment of cutaneous sensitivity occurs with aging [13,37]. This age-related decrease in sensitivity can reduce tactile perception, detection of noxious stimuli and tissue injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusions drawn from these studies suggest that proprioception decreases with aging is in part because of changes in muscle spindle function. In addition to that, advancing age leads to deficits in the processing of sensory input (myelin abnormalities, axonal atrophy, and declined nerve conduction velocity) [7,24,59,74] and neuromuscular performance decline. It has been shown that the older adult has fewer, but on average larger and slower motor units, resulting in motor unit reorganization [9,14,40,65,66].…”
Section: Mechanisms Of Proprioception Deterioration With Agingmentioning
confidence: 99%
“…The deterioration of myelin sheaths during aging may be due to a decrease in the expression of the major myelin proteins (P0, PMP22, MBP). Axonal atrophy, frequently seen in aged nerves, may be explained by a reduction in the expression and axonal transport of cytoskeletal proteins in the peripheral nerve (Verdu et al ., 2000). The incidence and severity of the age-related peripheral nerve changes seems to depend on the animal's genetic background.…”
Section: Effects Of Age On the Neuromuscular Junctionmentioning
confidence: 99%